(Re-)negotiating gender and class: New forms of cooperation among small-scale fishers in Tamil Nadu - Nitya Rao; R. Manimohan (United Nations Research Institute for Social Development (UNRISD), 2020)
This paper explores new forms of cooperation emerging among small-scale fishers along the east coast of Tamil Nadu, as responses to wider transformations in fisheries and coastal landscapes. Increased competition for limited open-access resources has resulted in a capitalization of fisheries, with those able to invest reaping benefits and others risking marginalization. In order to retain their status as fishers rather than labourers, and gain a voice in decision-making structures, dominated by the traditional elites, many small-scale fishers have been experimenting with new forms of cooperation involving the shared ownership of large boats, engines and other modern technologies. In the process, one finds shifts in class, caste, gender and generational roles, relations and identities. Based on data collected from a survey of 200 households and in-depth interviews with 20 households in Cuddalore district of Tamil Nadu, the paper explores the processes of negotiation and renegotiation of both gender and class identities, and their intersections. It considers whether, and how, new institutional practices and forms of cooperation (and conflict) are enabling a more equitable sharing of resources and benefits, and in which ways they are further entrenching inequalities.
Keywords: 330; Capitalization; cooperation; differentiation; fisheries; shares; Tamil Nadu